SYNCOPAL STATES IN THE PRACTICE OF PHYSICAL THERAPISTS IN ELDERLY PATIENTS (Physical Culture and Sport: Scientific Perspective, 2025)
The scientific work has reviewed domestic and foreign literary sources, Internet resources on the selected research issues, which allowed us to substantiate the relevance of the study. Analysis and synthesis of scientific information on the topic of the study showed that syncope is a serious medical problem with possible consequences of trauma. Fainting is caused by a decrease in systemic blood pressure and subsequent global hypoperfusion of the brain. Autoregulation of cerebral blood flow consists of a myogenic mechanism of vasoconstriction and vasodilation of vessels in response to pressure fluctuations. The factor that determines a relatively constant level of cerebral blood flow is the change in vessel diameter. In the elderly, atherosclerotic changes in the vessels lead to increased stiffness, especially in the carotid artery, and decreased vagus nerve tone, which causes most cases of syncope. Fainting is a serious medical problem with many consequences: injuries, the development of the patient's self-doubt, and a deterioration in the quality of life. Unresolved problems of syncope in elderly patients in the practice of physical therapists are identified, namely accurate diagnosis of the cause of syncope, teaching patients to recognize prodromes, preventing repeated falls and episodes of syncope, safe planning of physical activity, and improving first aid skills. In accordance with the purpose of the study, the types of syncope, syncope in the elderly, and measures to eliminate the immediate threat to the patient's life during physiotherapy intervention within the knowledge and competencies of the professional activity of a physical therapist were considered. It was recommended that further physiotherapy management of elderly patients with syncope be carried out after a comprehensive geriatric assessment, taking into account the patient's cognitive and functional characteristics.
Keywords: syncopal conditions; physical therapist; elderly patients